Magnetic anisotropy and the phase diagram of chiral MnSb2O6 - Werner, Johannes; Koo, Changhyun; Klingeler, Rüdiger (Physical review, 2016)
The magnetic phase diagram and low-energy magnon excitations of structurally and magnetically chiral MnSb2O6 are reported. The specific heat and the static magnetization are investigated in magnetic fields up to 9 and 30 T, respectively, while the dynamic magnetic properties are probed by X-band as well as tunable high-frequency electron spin-resonance spectroscopy. Below TN=11.5 K, we observe antiferromagnetic resonance modes which imply small but finite planar anisotropy showing up in a zero-field splitting of 20 GHz. The data are well described by means of an easy-plane two-sublattice model with the anisotropy field BA=0.02 T. The exchange field BE=13 T is obtained from the saturation field derived from the pulsed-field magnetization. A crucial role of the small anisotropy for the spin structure is reflected by competing antiferromagnetic phases appearing, at T=2 K, in small magnetic fields at BC1 ≈0.5 T and BC2=0.9 T. We discuss the results in terms of spin reorientation and of small magnetic fields favoring helical spin structure over the cycloidal ground state which, at B=0, is stabilized by the planar anisotropy. Above TN, short-range magnetic correlations up to ≳60 K and magnetic entropy changes well above TN reflect the frustrated triangular arrangement of Mn2+ ions in MnSb2O6.
Im Titel ist die Zahl "2" und "6" tiefgestellt